A review of potential candidate genes polymorphism responsible for schiz-ophrenia risk - Priya, Indu; Sharma, Sakshi; Sharma, Isar; Mahajan, Ritu; Kapoor, Nisha (International Journal of Scientific Research in Biological Sciences, 2018)
Schizophrenia (SCZ) is a strong heritable disorder that involves multiple gene combination, each conferring a little increase in the burden to the disease. Due to the complexity of disease, it is difficult to find susceptible genes and promising biomarker. The true etiology of SCZ is still not fully understood, however, recent studies on SCZ molecular genetics, with a focus on candidate genes approach affirms and predicate association with SCZ. Some investigators have reported the involvement of environment factors in the formation and progression of the Schizophrenia. Literature has been surveyed that reports association between genetic variation and SCZ also between genetic polymorphisms and clinical outcomes. The present study focuses on human populations to review SNPs of various genes which show best association with the disease. We have identified 60 published case control studies that have studied association of various SNPs in different population.